PERAN GURU DAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Fira Aulia Annur Rizky; Alvina Hermawaty; Ainaya Nafiza Nazali; Afif Rafi Alaudidin; I Ketut Mahardika; Rizka Elan Fadilah; Firdha Yusmar (Pendidikan Fisika FKIP UNEJ, 2022)
The lack of learning motivation in learners can be caused by several factors. One of them is the lack of role of the teacher in the teaching and learning process in schools. The difficulty of parents in accompanying children to learn is the background of the parents' education, economic level, and the absence of time. Learning motivation in students is very important because learning motivation has a behavioral influence on students in their learning activities. The research made uses the literature study method by reviewing several journals. In conclusion, the role of teachers and parents in increasing student learning motivation is by managing from learning time, understanding how students learn, building bonds with parents and teachers, providing effective and easily absorbed learning media, providing support for learning and doing assignments, providing opportunities for students to find interests and talents that exist in their identity, and also provide facilities both facilities and infrastructure that are feasible in learning students.